Peran Manajemen dalam Meningkatkan Efektivitas Organisasi - Eka Tripustikasari (Journal of New Trends in Sciences, 2025)
. This study aims to comprehensively analyze the role of management in enhancing organizational effectiveness. In the context of increasingly complex business dynamics, organizations require managerial approaches that are not only efficient but also adaptive to change. This research adopts a descriptive qualitative approach to examine classical to modern management theories, as well as core managerial functions such as planning, organizing, leading, and controlling. Through literature studies and conceptual observations, the research finds that organizational effectiveness is significantly influenced by the consistency and integration of managerial functions, particularly in the context of strategic leadership and efficient resource management. Moreover, the organization’s flexibility in responding to external environmental changes and its ability to create a collaborative and productive work culture are critical success factors. A case study of PT Astra International Tbk serves as concrete evidence of how strategic and structured management can generate sustainable competitive advantages and growth. By applying managerial functions in an integrated manner and aligning them with market and organizational needs, the company maintains superior performance. This research contributes to the development of management science, particularly in the context of organizational effectiveness. The study recommends strengthening managerial capacity, developing visionary leadership, and establishing a result-oriented control system as essential strategies for improving organizational performance